A New Look at the Daily Cycle of Trade Wind Cumuli. (16th October 2019) - Vial, Jessica; Vogel, Raphaela; Bony, Sandrine; Stevens, Bjorn; Winker, David M.; Cai, Xia; Hohenegger, Cathy; Naumann, Ann Kristin; Brogniez, Hélène
Abstract: A description of the daily cycle of oceanic shallow cumulus for undisturbed boreal winter conditions in the North Atlantic trades is presented. Modern investigation tools are used, including storm‐resolving and large‐eddy simulations, run over large domains in realistic configurations, and observations from in situ measurements and satellite‐based retrievals. Models and observations clearly show pronounced diurnal variations in cloudiness, both near cloud base and below the trade inversion. The daily cycle reflects the evolution of two cloud populations: (i) a population of nonprecipitating small cumuli with weak vertical extent, which grows during the day and maximizes around sunset, and (ii) a population of deeper precipitating clouds with a stratiform cloud layer below the trade inversion, which grows during the night and maximizes just before sunrise. Previous studies have reported that cloudiness near cloud base undergoes weak variations on time scales longer than a day. However, here we find that it can vary strongly at the diurnal time scale. This daily cycle could serve as a critical test of the models' representation of the physical processes controlling cloudiness near cloud base, which is thought to be key for the determination of the Earth's climate response to warming. Key Points: Trade wind cumuli exhibit a pronounced daily cycle, with an evening maximum near cloud base and a nighttime/dawn maximum near the inversion Cloud‐base cloudiness during undisturbed periods can be much more variable at the diurnal than at longer time scales The representation of the daily cycle of inversion clouds is particularly sensitive to resolution